KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS TEKS HASIL OBSERVASI SISWA KELAS VII SMPN 16 TEBO - Lisa Apriyenti; Novia Aurora; Afnita Afnita (CARAKA, 2019)
This study aims to determine the relationship of reading skills in the text of the observation report and the text writing skills of the observation results of the VII students of SMPN 16 Tebo. This type of research uses quantitative research. This research method is descriptive method with correlational design. The population is seventh grade students at SMPN 16 Tebo which are divided into 105 people into four classes. The sample of this study was 32 people. This study consisted of two variables, namely the independent variable (reading comprehension skills of the text from the seventh grade observation report of Tebo 16 Public High School) and (dependent variable (writing skill in the seventh grade of Tebo SMPN 16 observational report). observations, need to read comprehension skills from observation reports.